Crossmodal interactions during non-linguistic auditory processing in cochlear-implanted deaf patients. (October 2016) - Barone, Pascal; Chambaudie, Laure; Strelnikov, Kuzma; Fraysse, Bernard; Marx, Mathieu; Belin, Pascal; Deguine, Olivier
Abstract: Due to signal distortion, speech comprehension in cochlear-implanted (CI) patients relies strongly on visual information, a compensatory strategy supported by important cortical crossmodal reorganisations. Though crossmodal interactions are evident for speech processing, it is unclear whether a visual influence is observed in CI patients during non-linguistic visual–auditory processing, such as face–voice interactions, which are important in social communication. We analyse and compare visual–auditory interactions in CI patients and normal-hearing subjects (NHS) at equivalent auditory performance levels. Proficient CI patients and NHS performed a voice-gender categorisation in the visual–auditory modality from a morphing-generated voice continuum between male and female speakers, while ignoring the presentation of a male or female visual face. Our data show that during the face–voice interaction, CI deaf patients are strongly influenced by visual information when performing an auditory gender categorisation task, in spite of maximum recovery of auditory speech. No such effect is observed in NHS, even in situations of CI simulation. Our hypothesis is that the functional crossmodal reorganisation that occurs in deafness could influence nonverbal processing, such as face–voice interaction; this is important for patient internal supramodal representation.